A companion to Simone de Beauvoir - Hengehold, Laura; Bauer, Nancy, 1960- (Hoboken : Wiley, 2017)
The work of Simone de Beauvoir has endured and flowered in the last two decades, thanks primarily to the lasting influence of The Second Sex on the rise of academic discussions of gender, sexuality, and old age. Now, in this new Companion dedicated to her life and writings, an international assembly of prominent scholars, essayists, and leading interpreters reflect upon the range of Beauvoir's contribution to philosophy as one of the great authors, thinkers, and public intellectuals of the twentieth century. The Companion examines Beauvoir's rich intellectual life from a variety of angles-including literary, historical, and anthropological perspectives-and situates her in relation to her forbears and contemporaries in the philosophical canon. Essays in each of four thematic sections reveal the breadth and acuity of her insight, from the significance of The Second Sex and her work on the metaphysics of gender to her plentiful contributions in ethics and political philosophy. Later chapters trace the relationship between Beauvoir's philosophical and literary work and open up her scholarship to global issues, questions of race, and the legacy of colonialism and sexism. The volume concludes by considering her impact on contemporary feminist thought writ large, and features pioneering work from a new generation of Beauvoir scholars. Ambitious and unprecedented in scope, A Companion to Simone de Beauvoir is an accessible and interdisciplinary resource for students, teachers, and researchers across the humanities and social sciences.
Chapter 8 The Drama of Independence: Narcissism, Childhood, and the Family Complexes 1. The Character of Childhood and the Fruition of Freedom; 2. The Enigma of Narcissism; 3. Vital Insufficiency, Prematurity, and the Family Complexes; 4. The Dramas of Weaning and Intrusion; 5. Conclusion; Notes; References; Chapter 9 The Second Sexuality: Training in the Work of Simone de Beauvoir and Michel Foucault ; 1. Introduction; 2. Beauvoir on the Girl's Formation: The Existential Infant and the Girl's Vocation; 3. Foucault's Disciplinary Orthopedics and its Reception; 4. Beauvoir and Foucault; Notes.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Beauvoir, Simone de, -- 1908-1986.; Beauvoir, Simone de, -- 1908-1986.; PHILOSOPHY -- History & Surveys -- Modern; Electronic books